2009
DOI: 10.1007/s00424-009-0697-4
|View full text |Cite
|
Sign up to set email alerts
|

PKC epsilon facilitates recovery of exocytosis after an exhausting stimulation

Abstract: It has been well documented that protein kinase Cs (PKCs) play multifaceted roles in regulating exocytosis of neurotransmitters and hormones. But the isoform-specific PKC effects are still poorly elucidated mainly because of the large variety of PKC isoforms and the dubious specificity of the commonly used pharmacological agents. In the present study, based on overexpression of wild-type or dominant negative PKC epsilon, we demonstrate in neuroendocrine PC12 cells that PKC epsilon, but not PKC alpha, facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…they arrive from the inner cytosol to the subplasmalemmal region and retrieve back after some time. The mobility and trafficking dynamics of secretory vesicles directly relate to their fusion competence and their secretion kinetics (Degtyar et al 2007, Holz & Axelrod 2008, Zhang et al 2008, Xue et al 2009b. Subplasmalemmal leptin vesicles ( Fig.…”
Section: Compartmentalization Of Leptin and Resistinmentioning
confidence: 99%
“…they arrive from the inner cytosol to the subplasmalemmal region and retrieve back after some time. The mobility and trafficking dynamics of secretory vesicles directly relate to their fusion competence and their secretion kinetics (Degtyar et al 2007, Holz & Axelrod 2008, Zhang et al 2008, Xue et al 2009b. Subplasmalemmal leptin vesicles ( Fig.…”
Section: Compartmentalization Of Leptin and Resistinmentioning
confidence: 99%
“…A study reports that protein kinase C ε facilitates the recovery of the extent of exocytosis after a long stimulation in a phosphatidylinositol biphosphate-dependent manner. 102 The authors postulate that this might be used to enhance the rate of vesicle delivery and faster actin network reorganization. A quantitative investigation of the characteristics of spikes produced by chromaffin cells has led to the hypothesis that the duration and size of the fusion pore are determined by the features (size and topology at least) of the vesicle, and that the duration of the spike is characterized by the molecular factors of the cell membrane.…”
Section: Electrochemical Methods At Single Cellsmentioning
confidence: 99%
“…Biochemical evidence demonstrated that IQGAP1 can be phosphorylated by the kinase PKCε at its C-terminus, thereby relieving an autoinhibited fold, enhancing the binding of IQGAP1 to active CDC42 66 , and leading to attenuation of exocytosis 67 . PKCε has also been implicated in exocytosis by playing an essential role in the disassembly of actin filaments following docking and tethering of the vesicles 6870 . Since different stages of exocytosis require different actin organizations, these data suggest a dynamic interplay between PKCε, CDC42, and IQGAP in regulating actin dynamics.…”
Section: Coordination Of Cytoskeletal Cortical Interactions and Secrementioning
confidence: 99%